(untitled) (Journal of Bangladesh Academy of Sciences, 2018)
The paper reports the findings on the concentrations of heavy metals in ten different fish feed by using Atomic Absorption Spectrometer. The level of heavy metal concentrations (dry weight) in the fish feed ranged from 1.17 to 2.0, 2.33 to 4.67, 5.17 to 21.67, 106.67 to 363.3, 3.5 to 7.16, 3.83 to 21.2, 56.7 to 141.6 and 2.1 to 16.49 mg/kg of Cd, Co, Cu, Fe, Ni, Pb, Zn and Cr respectively. The concentrations of Fe, Pb, Co, Cr in different brands of fish feed exceeded the maximum permissible limits recommended by FAO/WHO and EU whereas the concentrations of Cd, Cu, Ni, Zn were within acceptable limits. Journal of Bangladesh Academy of Sciences, Vol. 42, No. 2, 207-210, 2018